Sensitive ADAR editing reporter in cancer cells enables high-throughput screening of small molecule libraries. Issue 4 (22nd December 2018) - Fritzell, Kajsa; Xu, Li-Di; Otrocka, Magdalena; Andréasson, Claes; Öhman, Marie
Abstract: Adenosine to inosine editing is common in the human transcriptome and changes of this essential activity is associated with disease. Children with ADAR1 mutations develop fatal Aicardi-Goutières syndrome characterized by aberrant interferon expression. In contrast, ADAR1 overexpression is associated with increased malignancy of breast, lung and liver cancer. ADAR1 silencing in breast cancer cells leads to increased apoptosis, suggesting an anti-apoptotic function that promotes cancer progression. Yet, suitable high-throughput editing assays are needed to efficiently screen chemical libraries for modifiers of ADAR1 activity. We describe the development of a bioluminescent reporter system that facilitates rapid and accurate determination of endogenous editing activity. The system is based on the highly sensitive and quantitative Nanoluciferase that is conditionally expressed upon reporter-transcript editing. Stably introduced into cancer cell lines, the system reports on elevated endogenous ADAR1 editing activity induced by interferon as well as knockdown of ADAR1 and ADAR2. In a single-well setup we used the reporter in HeLa cells to screen a small molecule library of 33 000 compounds. This yielded a primary hit rate of 0.9% at 70% inhibition of editing. Thus, we provide a key tool for high-throughput identification of modifiers of A-to-I editing activity in cancer cells.